IMPACTS OF A MULTISTAGE NETWORK ATTACKS: Submitted: February 18, 2024 , Revised: March 05, 2024 , Accepted: March 16, 2024 (International Journal of Engineering Management Science, 2024)
The identification and prevention of multistage network assaults have emerged as key concerns for organizations globally in the quickly changing field of cybersecurity. This study provides a thorough examination of current approaches, outlines their shortcomings, and suggests a future course for improving network defense mechanisms. The study takes into account the most recent findings and makes use of sophisticated network analysis methods to identify potential weaknesses and practical defenses.
Keywords: Cybersecurity, Network attacks, Prevention, Improved network